Letters to Ítala: the force of threat and the power of fiction in Performance Art (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article is presented as a letter written by a performer to another performer, Ítala Isis. The friendship between the two artists sets the tone for the conversation, which seeks to reflect on the effective possibilities of art in containing violence against black and vulnerable bodies in the city of Rio de Janeiro. Tragic events experienced by the two, such as the execution of Rio de Janeiro councilwoman Marielle Franco, are triggers for Actions that find in Felipe Ribeiro's thoughts on the power of threat and Jota Mombaça's thoughts on the power of fiction, ways for new forms of political life to take place.
Keywords: rerformance art; Rio de Janeiro; body figure; letters; political friendship